KEMAMPUAN PESERTA DIDIK KELAS VIII SMP NEGERI 1 TELAGA MENGIDENTIFIKASI UNSUR-UNSUR DRAMA DALAM PEMBELAJARAN BAHASA INDONESIA - Sri Gitawati Umar; Fatmah AR Umar; Herman Didipu (Jurnal Bahasa, Sastra, dan Budaya, 2020)
This study aims to describe the ability of eighth-gradersin SMP 1 state junior high school of telaga in identifying the elements of drama in Indonesia Language Subject, the factors that inhibit the ability, and solutions to the inhibitors. This descriptive research collectsthe data using ability tests and questionnaires to measure the students' ability in identifying the elements of drama, obtaining an average of 67 categorized as "less", It is evidenced from the ability to identify the theme with an average of 70 categorized as "less", the ability to identify the drama plot with an average of 71 categorized as "less", the ability to identify characterizations with an average of 68 categorized as "less", the ability to identify the background with an average of 72 categorized as "adequate", the ability to identify the dialog with an average of 58 categorized as "poor", the ability to identify the moralwith an average of 60 categorized as "poor". Furthermore, the inhibitorsof the abilities identified factors of students, school, facilities, and infrastructure influence, and the solutions to theseinhibitionsare to adapt to the characteristics of said factors. This research is concluded with thestudents' ability to identify the elements of drama in the "less" category